2015
DOI: 10.1002/stc.1738
|View full text |Cite
|
Sign up to set email alerts
|

Free vibrations of a two-cable network with near-support dampers and a cross-link

Abstract: SUMMARYVibration mitigation of cables is a crucial problem for cable-supported bridges. A hybrid method for cable vibration mitigation that combines cross-ties and dampers has been applied in engineering practice; however, the damping and frequency of this kind of system needs to be further assessed. In this paper, a system of two parallel cables with a cross-link and dampers located near the cable anchorage is proposed and analyzed. Based on displacement continuity and force equilibrium at the damper and spri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…i. As also shown in Figure 5a, when 1 is close to the value given in Equation (33), modal frequency veering occurs between adjacent symmetric modes. ii.…”
Section: Rigid Connectionsupporting
confidence: 73%
See 1 more Smart Citation
“…i. As also shown in Figure 5a, when 1 is close to the value given in Equation (33), modal frequency veering occurs between adjacent symmetric modes. ii.…”
Section: Rigid Connectionsupporting
confidence: 73%
“…[23][24][25][26] The number of cross-ties, as well as other key system parameters, have been studied in the context of a more complex cable network. 27 To increase the dissipation capacity of cable networks, hybrid techniques combining cross-ties and dampers have been proposed, [28][29][30][31] and more recently inerter element was integrated into the system by Sun et al 32 A particular hybrid system of a two-cable system with near-anchorage dampers was considered by Zhou et al 33 and Ahmad et al 34 Complex hybrid cable networks with various configurations have also been studied in the context of an existing bridge. 35 Nonlinearity of the cross-ties and stochastic responses of the cable networks have caught attention recently.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, some hybrid techniques have been further proposed. The idea of combining external dampers with cross-ties for cable vibration control was considered, which not only addresses the deficiencies of these two commonly used countermeasures but also still retains their respective merits [68][69][70][71][72][73]. A hybrid damper system, combining a viscous damper and a tuned mass damper, can overcome the shortcomings of single type of dampers and improve effectiveness and robustness in suppressing cable vibration [74].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, considerable studies have confirmed that the bending stiffness of the cable must be considered for the identification of the cable force through the dynamic method. However, there is still no exact equation to value the bending stiffness of these special structures [8,25,26].…”
Section: Bending Stiffness Of the Cablementioning
confidence: 99%